2001
DOI: 10.1164/ajrccm.164.10.2010096
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factors C3a and C5a Are Increased in Bronchoalveolar Lavage Fluid after Segmental Allergen Provocation in Subjects with Asthma

Abstract: Allergic asthma is thought to be the result of an inappropriate specific immune response against common environmental antigens. However, studies of animal asthma models have also linked the innate immune system, in particular complement factors C3a and C5, to murine airway hyperresponsiveness. Because the possible role of these anaphylatoxins in patients with asthma is not understood, we tested the hypothesis that C3a and C5a will increase in the bronchoalveolar lavage (BAL) fluid of patients with asthma after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 13 publications
9
128
0
Order By: Relevance
“…Using C3aR Ϫ/Ϫ mice, though, the C3aR has been shown to play an unexpectedly important role in experimental models of asthma (44). Furthermore, levels of C3a and C5a are elevated in bronchoalveolar lavage fluid from patients with asthma (45). The role of the alternative pathway has been studied recently in a mouse model of airway hyperresponsiveness (46).…”
Section: Asthmamentioning
confidence: 99%
“…Using C3aR Ϫ/Ϫ mice, though, the C3aR has been shown to play an unexpectedly important role in experimental models of asthma (44). Furthermore, levels of C3a and C5a are elevated in bronchoalveolar lavage fluid from patients with asthma (45). The role of the alternative pathway has been studied recently in a mouse model of airway hyperresponsiveness (46).…”
Section: Asthmamentioning
confidence: 99%
“…There is substantial evidence that complement pathways are activated in the lungs of individuals with asthma (6)(7)(8). Specifically, it has been shown that C3a and C5a levels are higher in the BAL of individuals with asthma compared with healthy control subjects at baseline (8).…”
Section: Mechanisms Of Complement Activation In Asthmamentioning
confidence: 99%
“…Similar effects have been shown for C3a. Specifically, several groups have now shown that deficiencies in C3 (21,22) or the C3aR (7,23,24) protect against the development of allergen-driven AHR. Likewise, the AHR induced by exposure to several environmental stimuli, including RSV (11), particulate matter (22), and ozone (9), has been shown to be C3-dependent.…”
Section: Complement Pathway Regulation Of Allergic Effector Pathwaysmentioning
confidence: 99%
“…Increased levels of C3a in the circulation have been found in diseases such as adult respiratory distress syndrome (24), asthma (25), psoriasis, and atopic dermatitis (AD) (26). C3 fragments are also found intralesionally in inflammatory diseases such as psoriasis (27), eczema (28), and asthma (19,29). Recently, C3b deposition was detected in the stratum corneum of the lesions of psoriasis vulgaris, and a cytoplasmic distribution of C3b as well as C3a was observed in the subcorneal to spinous KCs of allergic contact dermatitis, AD, and psoriatic lesional KCs (30).…”
mentioning
confidence: 99%